A Brief Review of Ophthalmology In Indian Classical Literature - Vardhan, Prabhakar; Sharma, Sanjeev; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2022)
Shalakya Tantra existed from ancient times, however not clearly. In pre-Vedic India, copper and bronze rods (Shalaka) were used to apply Anjanas (collyria) to avoid eye problems. Even though Shalakya tantra isn’t mentioned in Vedic literature, eye anatomy and illnesses were known and treated in that age. Rigveda, the oldest known treatise, mentions eye illness treatment. Yajurveda mentions various eye components. Atharvaved addresses Netra’s synonyms, eye disorders like akshi-yakshma, and their symptoms. In Brahmanas and Upanishadas, the eye and its functions are described, along with blindness, netrasrava, and blindness cure. Shalakya word isn’t mentioned. Shalakya Tantra was defined in the Samhita period, when Ayurveda developed in eight branches. Eye illnesses induced by Vata, Pitta, Shleshma, and Sannipata are listed in Lalitvistara text of Buddhist literature. Panini calls Shalakya experts ’Shalakkii’ and describes timira and arma. Eye illnesses aren’t discussed in Agnivesha Tantra (Charak Samhita) in detail. In carak samhits Eye illnesses are characterised by doshic predominance and their origin and therapy are outlined. First 19 chapters of Shalakya are on ophthalmology. Sushruta Samhita describes local ocular therapeutic measures such as Kriya kalpa (Tarpana, Putpaka, Seka, Aschyotana and Anjana) and surgical techniques for treating eye problems. His eye surgical contributions are impressive. He discovered cataract surgery perhaps first. Vagbhatta detailed newer therapy techniques as Vidalaka, Gudana, and Sandhavanjana, along with new formulations and procedures. Acharya Madhava characterised ocular ailments after Sushruta, adding Kunchana and Pakshmashata. Bhavaprakasha. Yog Ratnakar, etc. described ophthalmology similarly to Sushruta Samhita with formulations for their treatment.